Disharmonization of Wakalah Contract in Law Number 34 of 2014 and DSN-MUI Fatwa Number 122/DSN-MUI/II/2018 - Hasan Ali, A.M (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2019)
BPKH, as a Hajj financial management institution in Indonesia, plays an essential role in evolving the Hajj Fund. With the biggest potential of the Muslim population in the world, Indonesia can administrate hajj finances in a larger scope by investing them on business lines, which are in accordance with sharia principles. However, the wakalah contract, as the foundation of agreement between the prospective pilgrims and the BPKH institution, is interpreted differently by Law Number 34 of 2014 and the DSN-MUI Fatwa Number 122/DSN-MUI/ II/2018. As a consequence, the difference causes disharmony between the two laws. The different interpretations of these regulations have led to some legal consequences. These are related to the determination of the responsible parties in the case of the failure in investment, which involve the government or BPKH as the hajj fund administrators. This paper is based on a qualitative inquiry, using regulations as the primary sources, supported by non-legal materials. Content analysis with normative juridical themes is used to analyze the legal system and principles. BPKH sebagai lembaga pengelola keuangan haji di Indonesia memiliki peranan penting dalam mengembangkan Dana Haji. Dengan potensi umat Islam terbesar di dunia, Indonesia dapat mengelola keuangan haji dalam ruang lingkup yang lebih besar dengan menginvestasikan keuangan haji pada lini usaha yang sesuai dengan prinsip-prinsip syariah. Namun akad wakalah sebagai dasar yang digunakan antara para calon jamaah haji kepada lembaga BPKH diinterpretasikan berbeda antara Undang-Undang No. 34 Tahun 2014 dengan Fatwa DSN-MUI No. 122/ DSN-MUI/II/2018 sehingga menimbulkan disharmonisasi pada kedua perundang-undangan tersebut. Perbedaan interpretasi peran wakil pada kedua perudang-undangan ini menimbulkan konsekuensi hukum berupa perbedaan penerima tanggung jawab yang melibatkan pemerintah maupun BPKH selaku pengelola keuangan haji apabila mengalami kegagalan investasi. Penelitian ini menggunakan metode kualitatif dengan data sekunder berupa peraturan perundangan-undangan, buku terkait, dan bahan non hukum. Teknik yang digunakan adalah content analysis dengan tema penelitian yuridis normatif yang menganalisis asas-asas dan sistematika hukum.